The Relationship of Self Regulated Learning with Academic Adjustment of Seventh Grade Santri of Pondok Pesantren - Hannani, Ulfa; Ajisuksmo, Clara (TAZKIYA Journal of Psychology, 2021)
Academic adjustment is an important thing for students, especially seventh graders at Miftahul Ulum Islamic Boarding School, one of the modern-based Islamic boarding schools that combines the national education curriculum and the cottage curriculum. In early adolescence, students have begun to develop cognitive strategies and adjust behavior to the academic environment. The ability of students to regulate cognitive and behavior in learning is called self-regulated learning. The purpose of this study was to determine the relationship between self-regulated learning and the academic adjustment amongst seventh grade students of Miftahul Ulum Islamic Boarding School. The research method used in this research was mixed methods. Quantitative data was collected from 160 students through The Motivated Strategies of Learning Questionnaire Scale (MSLQ) to measure self-regulated learning and Student Adaptation to College Questionnaire (SACQ) to measure academic adjustment. While in the qualitative approach, group interviews students were conducted into three group based on the level of the self-regulated learning group and academic adjustment. The result reveals that there was a significant positive relationship between self-regulated learning and the academic adjustment of seventh grade students at Miftahul Ulum Islamic Boarding School (r = 0,561; p < 0,001) indicating that students who had high self-regulated learning also had high academic adjustment at Miftahul Ulum Islamic Boarding School. The group discussion found interesting results where students who have good motivation, cognitive strategies and learning behavior strategies, then adjust themselves to academic demands at Miftahul Ulum Islamic Boarding School is also good.